TRINICON-BSS system incorporating robust dual beamformers for noise reduction - Anderson, Craig; Meier, Stefan; Kellermann, Walter; Teal, Paul D.; Poletti, Mark A. (IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP), 2015)
In this paper, a method of adaptive noise suppression combining spatially robust fixed beamforming and the TRINICON blind source separation algorithm is presented. A multichannel sensor array is first processed using complementary fixed beamformers into maximum and minimum SINR channels. The channels form the inputs to a single 2×2 second-order statistics TRINICON-BSS system which adaptively compensates for imperfections of the fixed beamformer design relative to the acoustic scenario. It is demonstrated that integrating the TRINICON-BSS algorithm leads to improved SINR performance over the initial imperfect beamformer design, and achieves a performance comparable to a perfect MVDR beamforme
Keywords: Robust beamforming; Adaptive filtering; Blind source separation